A STUDY OF KNITTED FABRICS PROPERTIES ABOUT THEIR INFLUENCE IN PATTERN MAKING OF LADIES’ DRESSES - Tanya Peneva (Applied Researches in Technics, Technologies and Education, 2019)
The article presents a study and analysis of properties of knitted fabrics about their influence in the process of pattern making of ladies dresses in different ‘types of silhouettes. The presented study uses the Standard NEXT TM 21a (knit) method for testing the stretchability and return of a cross-knit knitted fabric. This method is used in the accredited laboratory of one of Europe's largest fabrics manufacturers - E. Miroglio Ltd, which is made by clothing manufacturers and retailers. On the base of the obtained values, correction coefficients are determined which will be applied in pattern making of ladies' dresses in different types of silhouettes.